ANALISIS DAMPAK PENERAPAN PSAK 221 TERHADAP PENGAKUAN,PENGUKURAN SELISIH KURS, DAN KUALITAS PELAPORAN KEUANGAN ENTITAS MULTINASIONAL DI INDONESIA - Florentino Edoardo Christian Uwong; Azel Zahran Arsyfandy; Naomi Veronika Aprilia; Duta Achmad Hartono; Rinny Meidiyustiani (Jurnal Ilmiah Akuntansi, 2026)
This study presents a critical analysis of the implementation of Statement of Financial Accounting Standards (PSAK) 221 regarding the Effects of Changes in Foreign Exchange Rates, which is a substantive adoption of IAS 21 and replaces the previous provisions in PSAK 10. Given the increasing exposure of Indonesian entities to exchange rate fluctuation risks, compliance with PSAK 221 is important to ensure the transparency and relevance of financial statements. This study aims to analyze the technical provisions of PSAK 221 related to the definition, recognition, measurement, and presentation of foreign exchange transactions and the description of overseas business activities, and to evaluate the effect of accounting treatment of exchange differences—transactional exchange differences (recognized in Profit or Loss) versus translation exchange differences (recognized in Other Comprehensive Income/OCI)—on net profit volatility and the informative value of financial statements. The method used is a descriptive qualitative case study based on document analysis (analysis of accounting policies and Notes to the Financial Statements of entities with significant foreign currency exposure, for the period 2023–2024). The main findings show that PSAK 221 reinforces the determination of functional currency and requires the separation of exchange rate differences based on their source, which in turn improves the quality and informative value of profit while changing the pattern of profit volatility. The contribution of this research is a more detailed technical interpretation and analysis of strategic implications.